Inovasi Kurikulum dalam Upaya Meningkatkan Mutu Pendidikan di Indonesia - Aisyah Faradhilah Yasmin; Atika Maulidina Hs (Jurnal Pena Karakter : Jurnal Pendidikan Anak dan Karakter, 2023)
Curriculum is a very important role in education aimed at directing it in a better direction.  Curriculum  implementation  is  developed  in schools  to  suit circumstances and needs. These things are related to each other and become a reference for all parties who play a role in implementing the curriculum. The curriculum  process  includes  planning,  organizing,  implementing,  monitoring and  evaluating  in  curriculum  development.  Evaluation  as  a  measure  of curriculum achievement. Education is a human effort to improve knowledge to become better. The purpose of this article is to develop an innovative curriculum in an effort to improve the quality of education.